Joint Influences of Erroneous Channel Information, Fading Severity, Jamming Suppression Error, Energy Harvesting Non-Linearity on Underlay Relaying Networks - Le-Thanh, Toi; Ho-Van, Khuong (Arabian journal for science and engineering (2011), 2022)
This paper considers an underlay relaying network where a cognitive relay performs decode-and-forward operation to aid communication between a cognitive source-destination pair. Transmit powers of cognitive users are subject to both interference and peak transmit power constraints. To stimulate support, the relay merely spends power scavenged from source signals with realistic non-linear energy harvester for its operation. Additionally, to secure secret transmission of both the source and the relay, this paper proposes to merge jamming signals with secret ones before their transmission. Relied on practical observations that jamming signals and channel state information at legitimate receivers may not be suppressed and estimated perfectly, respectively, this paper analyzes system performance under inaccuracies of jamming suppression and channel estimation. Purposively, this paper analyzes security-reliability trade-off of underlay relaying networks under joint practical influences of erroneous channel information, Nakagami- m fading severity, jamming suppression error, energy harvesting non-linearity, and power constraints of cognitive users. Towards this end, explicit expressions of intercept and outage probabilities are first derived. Then, they are used to quickly generate numerous results so as to withdraw interesting findings. More specifically, the proposed jamming strategy experienced the trade-off between security and reliability as well as reliability/security saturation at high peak transmit power. Additionally, channel estimation error, fading severity, jamming suppression error, and energy harvesting non-linearity significantly impact system performance. Nonetheless, system parameters can be set properly to achieve different security levels and prevent absolute outage.